2018
DOI: 10.21873/anticanres.12231
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Expression of Human Epidermal Growth Factor Receptor 2 (HER2) in Gastric and Gastroesophageal Junction Adenocarcinoma Using IHC and Dual-ISH

Abstract: The 12.5% overall overexpression/amplification in gastric and GEJ adenocarcinomas is in concordance with previous reports. No correlation was found between tumor stage and HER2 overexpression/amplification. Determination of HER2 in limited tissue samples benefits from combinational IHC and ISH testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The detection results are affected by many factors, as well as the quality control of the laboratory and the interpretation of staining results. Some studies indicated that the expression rate of HER2 protein was significantly different from 6% to 34% [ 18 21 ]. In our research, HER2 protein was detected by combining the positive intensity and the positive area, which was divided into extensive staining, partial staining, and focal staining.…”
Section: Discussionmentioning
confidence: 99%
“…The detection results are affected by many factors, as well as the quality control of the laboratory and the interpretation of staining results. Some studies indicated that the expression rate of HER2 protein was significantly different from 6% to 34% [ 18 21 ]. In our research, HER2 protein was detected by combining the positive intensity and the positive area, which was divided into extensive staining, partial staining, and focal staining.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical analysis was performed as previously described ( Dominguez et al, 2018 ). The tumor or normal tissues were collected and perfused with 10% formaldehyde solution for 24 h at 4°C, followed by embedment in paraffin.…”
Section: Methodsmentioning
confidence: 99%